The heat pump wave - Toleikyte, Agne,Roca Reina, Juan Carlos,Volt, Jonathan,Carlsson, Johan,Lyons, Lorcan,Gasparella, Andrea,Koolen, Derck,De Felice, Matteo,Tarvydas, Dalius,Czako, Veronika,Koukoufikis, Giorgos,Kuokkanen, Anna,Letout, Simon (Publications Office of the European Union, 2023)
Decarbonisation of heating is a key priority of the EU's climate agenda, given that the building sector is responsible for 36% of total greenhouse gas emissions. Heat pumps play a central role in enabling the transition towards a climate-neutral society, and are also seen as a crucial tool in achieving independence from foreign oil and gas sources. The EU has set out a plan to quickly ramp up the manufacturing and installation of heat pumps. This study examines the potential impacts arising from this scale-up of heat pump installations. The European Building Energy Model (EBEM), an in-house bottom-up building model, has been developed to analyse current and future energy trends based on disaggregated building stock. The model accurately estimates and compares specific energy consumption and CO2 emissions, taking into account parameters such as heating type, insulation level and climatic region. The analysis shows that replacing 30 million fossil fuel individual boilers in residential dwellings with heat pumps would reduce the EU's gas and oil consumption by 36% in these dwellings. In the large majority of cases, switching from a fossil fuelled boiler to a heat pump will result in lower bills for heating. While the additional heat pumps will deliver more stress to the power grids, the impact is relatively modest and can be reduced, or even alleviated, by activating demand-side flexibility measures. The study also concludes that a rapid scale-up of heat pumps will require more and higher skilled workers across the whole value chain. The EU's heat pump supply is chain is vulnerable in a few areas, including a large dependence on imported compressors and semiconductors. Furthermore, there is a clear risk of financially vulnerable groups being excluded from this transition without targeted financial support. Finally, the EU is currently a leader in the production of several heat pump segments, but competition from American and Asian companies, particularly China, is rapidly increasing. Nevertheless, the EU is well placed to benefit economically from increased focus on heat pumps.
10.2760/27877
Keywords: Graue Literatur; Wärmepumpe; Strommarkt; Lieferkette; Internationaler Wettbewerb; Dekarbonisierung; EU-Energiepolitik; EU-Staaten; building services; heat pump; reduction of gas emissions; EU energy policy; energy grid; energy market; energy technology; energy poverty; competitiveness; EU Member State; research report